The Social Problems of an Industrial Civilisation (excerpt) - Mayo, Elton (Journal of Economic Sociology, 2024)
His forthcoming work, “Social Problems of Industrial Civilization,” published by the Gaidar Institute, includes a section dedicated to political challenges. During his tenure as a professor of industrial studies at Harvard University while working on “Social Problems of Industrial Civilization,” Mayo’s contributions to industrial sociology significantly influenced the development of this field. The book interprets critical issues of the industrial era through Mayo’s perspectives on the role of social sciences in addressing these challenges. A central theme is the facilitation of group cooperation within key industrial sectors. The author synthesizes insights gained from industrial research and proposes preliminary conclusions regarding the crucial role of interpersonal relationships in industry. The Journal of Economic Sociology features the first chapter titled “The Dark Side of Progress,” wherein Professor Mayo critically examines the imbalance present in systemic research. This imbalance is characterized by an overemphasis on technical and material aspects, neglecting the human and social dimensions in favor of unsystematic evaluations.